Dimension Analysis Of The Emergency Spillway Of Tirawan Dam With The Application Of The System Dynamic Model - Awan Risdiyanto; Adi Prawito (U Karst, 2022)
Tirawan Dam emergency spillway is planned to be able to drain the initial flood discharge when the gate above the main spillway is closed so that there will be sufficient time to open the gate to pass the peak flood discharge through the spillway safely. The emergency spillway elevation is designed to accommodate maximum water as a natural reserve during the dry season. This study aims to analyze the factors that play a role in emergency spillway design in meeting the availability of optimal raw water storage and increasing the safety factor against flooding using a simulation modeling method with the help of the Vensim PLE program. The modeling is made in three stages. The first is the analysis of the system model, the second is the creation of a caustic diagram, and the third stage is the simulation of the model and scenario model. The simulation results of this model scenario obtained an effective emergency spillway elevation of +69.50 m and a width of 20 m. The spillway can pass the Q1000 design flood without the control gate operation with a freeboard of 0.41 m with a raw water reserve of 240,649.69 m3. From the simulation results, it is also known that the operation of the main spillway serves to add a safety factor to the discharge capacity of the flood discharge during an emergency condition and cannot be operated to optimize the reservoir.